THE EFFECT OF ORALLY ADMINISTERED COENZYME Q10 ON THE VIABILITY OF RANDOM SKIN FLAP IN NICOTINE EXPOSED WISTAR RATS - Agustina, Wilma; Budi, Agus Santoso; Rizaliyana, Sitti (Jurnal Plastik Rekonstruksi, 2023)
Introduction : Nicotine was assumed to be the cause of compromised flap. The administration of antioxidants can eliminate such effect, and one of the most promising antioxidants is Coenzyme Q10. The research aims to find the effect of orally administered Coenzyme Q10 on the viability of random skin flaps in nicotine-exposed wistar rats. Method : Twenty-seven white rats (Rattus norvegicus) were assigned in three groups. The first group received no nicotine, while the other two groups were nebulized with nicotine for 4 consecutive weeks, and treated as random skin flaps. In third group, Coenzyme Q10 was administered for 7 days. Then, a standard histopathological staining and vascular endothelial growth factor (VEGF) measurement were performed on flap sample to examine the extent of neovascularization and VEGF cell expression. Result : The average number of capillaries in group I was 5.33 ± 1.323, in group II was 5.89 ± 0.782, and in group III was 7.78 ± 2.587. There was no significant difference (p = 0.317, 95% CI) in groups I and II of VEGF expression. However, significant differences were found in the intensity of VEGF (p = 0.009, 95% CI) in groups I and group III, and in groups II and group III (p = 0.011, 95% CI). Thus, the intensity was stronger on the subject with coenzyme Q10 compared with the other two groups. Conclusion: Coenzyme Q10 increases the viability of random flaps by increasing the number of capillaries and VEGF expression.